Digital Da'wah and Religious Authority: A Narrative Review of Islamic Preaching in the Social Media Era - 'Ulyan, Mohammad (Yayasan Sinergi Kawula Muda, 2023)
This narrative review examines the transformative role of social media in contemporary Islamic preaching, focusing on Southeast Asia with an emphasis on Indonesia. The study aims to understand how digital platforms reshape da'wah practices, redefine religious authority, and facilitate inclusive discourse. Using a structured literature review method, sources were collected from databases including Scopus, Google Scholar, DOAJ, JSTOR, and ProQuest, employing keywords such as